Gaseous 3-pentanol primes plant immunity against a bacterial speck pathogen, Pseudomonas syringae pv. tomato via salicylic acid and jasmonic acid-dependent signaling pathways in Arabidopsis - Song, Geun C.; Choi, Hye K.; Ryu, Choong-Min (Frontiers in Plant Science, 2015)
3-Pentanol is an active organic compound produced by plants and is a component of emitted insect sex pheromones. A previous study reported that drench application of 3-pentanol elicited plant immunity against microbial pathogens and an insect pest in crop plants. Here, we evaluated whether 3-pentanol and the derivatives 1-pentanol and 2-pentanol induced plant systemic resistance using the in vitro I-plate system. Exposure of Arabidopsis seedlings to 10 μM and 100 nM 3-pentanol evaporate elicited an immune response to Pseudomonas syringae pv. tomato DC3000. We performed quantitative real-time PCR to investigate the 3-pentanol-mediated Arabidopsis immune responses by determining Pathogenesis-Related (PR) gene expression levels associated with defense signaling through salicylic acid (SA), jasmonic acid (JA), and ethylene signaling pathways. The results show that exposure to 3-pentanol and subsequent pathogen challenge upregulated PDF1.2 and PR1 expression. Selected Arabidopsis mutants confirmed that the 3-pentanol-mediated immune response involved SA and JA signaling pathways and the NPR1 gene. Taken together, this study indicates that gaseous 3-pentanol triggers induced resistance in Arabidopsis by priming SA and JA signaling pathways. To our knowledge, this is the first report that a volatile compound of an insect sex pheromone triggers plant systemic resistance against a bacterial pathogen.